The cost effectiveness of rotavirus vaccination in Iran. Issue 3 (3rd March 2016) - Mousavi Jarrahi, Yasaman; Zahraei, Seyed Mohsen; Sadigh, Nader; Esmaeelpoor Langeroudy, Keyhan; Khodadost, Mahmoud; Ranjbaran, Mehdi; Sanjari Moghaddam, Ali; Besharat, Mehdi; Mosavi Jarrahi, Alireza
ABSTRACT: Rotavirus is the most common cause of severe diarrhea leading to hospitalization or disease-specific death among young children. Effective vaccines have recently been approved and successful vaccination program implemented. The aim of this study was to evaluate the cost effectiveness of mass rotavirus vaccination program in Iran. We developed a Markov model that reflects key features of rotavirus natural history. Parameters of the model were assessed by field study or developed through literature search and published data. We applied the model to the 2009 Iranian birth cohort and evaluated the cost-effectiveness of including the rotavirus vaccine (Rotarix®) into Iranian expanded immunization program (EPI). With an estimated hospitalization rate of 0.05 and outpatient rate of 0.23 cases per person-year, vaccinating cohort of 1231735 infants in Iran with 2 doses of (Rotarix®), would prevent 32092 hospitalizations, 158750 outpatient visits, and 1591 deaths during 5 y of follow-up. Under base-case assumption of $10 cost per course of vaccine, the vaccination would incur an extra cost of $1, 019, 192 from health care perspective and would avert 54680 DALYs. From societal perspective, there would be $15, 192, 568 saving for the society with the same averted DALYs. The incremental cost effectiveness ratio showed a cost of $19 US dollars per averted DALY from health care perspective and a saving of $278 US dollars for each averted DALY from societal perspective. Introducing rotavirus vaccine into EPI program would be highly cost-effective public health intervention in Iran.